Comparison of Modified Blumgart pancreaticojejunostomy and pancreaticogastrostomy after pancreaticoduodenectomy. Issue 3 (March 2016) - Wang, Shin-E.; Chen, Shih-Chin; Shyr, Bor-Uei; Shyr, Yi-Ming
Abstract: Background: The aim of this study was to compare perioperative outcomes after Blumgart pancreaticojejunostomy (PJ) and pancreaticogastrostomy (PG) for pancreatic-enteric reconstruction following pancreaticoduodenectomy. Methods: Data of patients undergoing Blumgart PJ and PG were retrieved from prospectively-collected database. Matched patients in each surgical groups were included based on the Callery risk scoring system for clinically relevant postoperative pancreatic fistula (CR-POPF) (grades B and C). Surgical parameters and risks were compared between these two groups. Results: A total of 206 patients undergoing PD were included. Blumgart PJ was associated with shorter postoperative hospital stay (median (range) 25 (10–99) vs. 27 (10–97) days, P  = 0.022). There was no surgical mortality in the Blumgart PJ group, but a 4.9% perioperative mortality in the PG, P  = 0.030. The CR-POPF by Blumgrt PG is significantly lower than that by PG for overall patients (7% vs. 20%, P  = 0.007), especially for those in intermediate fistula risk zone (6% vs. 21%, P  = 0.048) and high fistula risk zone (14% vs. 47%, P  = 0.038). Conclusions: Blumgart PJ is superior to PG in terms of pancreatic leakage and surgical mortality. Blumgart PJ can be recommended for pancreatic reconstruction after PD for all pancreatic remnant subtypes.